NHC-catalyzed chemoselective reactions of enals and aminobenzaldehydes for access to chiral dihydroquinolines - Wu, Shuquan (2020)
An N-heterocyclic carbene (NHC)-catalyzed reaction between α-bromoenals and 2-aminoaldehydes has been developed. Key steps include chemoselective reaction of the NHC catalyst with one of the aldehyde substrates (the bromoenal) to eventually generate an α,β-unsaturated acylazolium intermediate. Addition of the nitrogen atom of aminoaldehyde to the unsaturated azolium ester intermediate followed by intramolecular aldol reaction, β-lactone formation, and decarboxylation leads to chiral dihydroquinolines with high optical purity. The dihydroquinoline products, which are quickly prepared by using this method, can be readily transformed into a diverse set of functional molecules such as pyridines and chiral piperidines.